1998
DOI: 10.1038/sj.ejcn.1600611
|View full text |Cite
|
Sign up to set email alerts
|

Dietary assessment in the elderly: validation of a semiquantitative food frequency questionnaire

Abstract: Objective: The study was conducted to assess the relative validity of a 170-item semiquantitative food frequency questionnaire (SFFQ) adapted for use in the elderly. Design and subjects: The study was carried out in a sample of 80 men and women aged 55±75 y participating in a community based prospective cohort study in Rotterdam, The Netherlands. The two-step dietary assessment comprised a simple self-administered questionnaire (20 min) followed by a structured interview with trained dietitians (20 min) based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
224
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(242 citation statements)
references
References 31 publications
(28 reference statements)
13
224
1
1
Order By: Relevance
“…The consistency of the 7DD, HLQ and FFQ in the present analysis of alcohol and risk of CHD is aligned with the results of previous validation studies, in which good agreement was found among self-reported instruments (26)(27)(28)(29)(30)(31) . Some of the correlation between self-reported instruments may be attributable to within-person error (32) .…”
Section: Discussionsupporting
confidence: 88%
“…The consistency of the 7DD, HLQ and FFQ in the present analysis of alcohol and risk of CHD is aligned with the results of previous validation studies, in which good agreement was found among self-reported instruments (26)(27)(28)(29)(30)(31) . Some of the correlation between self-reported instruments may be attributable to within-person error (32) .…”
Section: Discussionsupporting
confidence: 88%
“…The total number of women in the study was 3432, of whom 750 were randomly selected for a subsample participating in detailed examinations including measurement of bone mineral density and dietary records and FFQ. Dietary data used in the present study were collected at study year 3 …”
Section: Participantsmentioning
confidence: 99%
“…Few studies have estimated the use and validity of FFQ in nutrient intake estimation in elderly populations (1)(2)(3) . However, determining nutrient intakes is critical in examining the effect of nutrition on health and disease.…”
mentioning
confidence: 99%
“…Second, a dietary assessment was done by a dietician during a visit of the subject to the research facility that took place about 22 days after the first step. (21) …”
Section: Clinical Examinationmentioning
confidence: 99%